Predicting Hepatic Steatosis in Living Liver Donors via Noninvasive Methods. Issue 7 (February 2016) - Kim, Jong Man; Ha, Sang Yun; Joh, Jae-Won; Sinn, Dong Hyun; Jeong, Woo Kyung; Choi, Gyu-Seong; Gwak, Geum Youn; Kwon, Choon Hyuck David; Kim, Young Kon; Paik, Yong Han; Lee, Joon Hyeok; Lee, Won Jae; et al.
Abstract : Abstract: Hepatic steatosis assessment is of paramount importance for living liver donor selection because significant hepatic steatosis can affect the postoperative outcome of recipients and the safety of the donor. The validity of various noninvasive imaging methods to assess hepatic steatosis remains controversial. The purpose of our study is to investigate the association between noninvasive imaging methods and pathology to detect steatosis in living liver donors and to propose a prediction model for hepatic steatosis. Liver stiffness measurements (LSMs) and controlled attenuation parameter values in vibration controlled transient elastography, ultrasonography, computed tomography (CT), and magnetic resonance imaging were used as pretransplant screening methods to evaluate living liver donors between 2012 and 2014. Only 1 pathologist assessed tissue sample for hepatic steatosis. The median age of the 79 living donors (53 men and 26 women) was 32 years (16–68 years). The CT liver–spleen attenuation (L–S) difference and the controlled attenuation parameter values were well correlated with the level of hepatic steatosis on liver pathology. Multivariate analysis showed that liver stiffness measurement (LSM) (β =  0.903; 95% CI, 0.105–1.702; P  = 0.027) and the CT L to S attenuation difference (β = −3.322; 95% CI, −0.502 to −0.142; P  = 0.001) were closely associated with hepatic steatosis. We generated the following equation to predict total hepatic steatosis: Hepatic steatosis = 0.903 × LSM – 0.322 × CT L to S attenuation difference (AUC = 86.6% and P  = 0.001). The values predicted by the equation correlated well with the presence of hepatic steatosis ( r  = 0.509 and P  < 0.001). The combination of nonenhanced CT L to S attenuation difference and transient elastography using vibration controlled transient elastography provides sufficient information to predict hepatic steatosis in living liver donor candidates.